Learning preferences in Generation Z college students - Sánchez-Altamirano, Fernando Rogelio (2025)
Objective. This study aimed to identify the learning preferences of Generation Z students enrolled in universities in the Northern Macroregion of Peru during 2022. Methodology. A non-experimental, cross-sectional, descriptive research design was employed. The sample consisted of 463 Generation Z students from faculties of economic and administrative sciences at three universities. A questionnaire adapted from Nicholas (2020) and contextualized was administered; it included 12 indicators of learning methods and 7 resources for classroom learning, with Likert-scale responses. Descriptive and inferential statistical analyses were performed, including ANOVA and Tukey’s Post Hoc tests. Results. The findings indicate statistically significant differences in preferences for learning methods and support resources, with a marked preference for certain methods and resources over others. The methods most highly rated as having the highest means were ‘in-class problem-solving exercises’ (80.26) and ‘combination of academic activities’ (81.54), while the most preferred learning resources included ‘reading material before class’ (73.16) and ‘lecture sessions with slides’ (73.88). Conclusions. Generation Z students show a clear preference for active, interactive, collaborative, and technology-based learning methods, as well as learning resources that are visual, multimedia, and participatory.